Assessing access to paediatric trauma centres in Canada, and the impact of the golden hour on length of stay at the hospital: an observational study. Issue 1 (8th January 2016) - Amram, Ofer; Schuurman, Nadine; Pike, Ian; Friger, Michael; Yanchar, Natalie L
Abstract : Objectives: In Canada injuries are a leading cause of death and morbidity among the paediatric population. Trauma systems have been established across North America to provide comprehensive injury care and to lead injury control efforts. However, not all populations have equal access to trauma care services. This is an observational study with the aim of assessing the impact of geographical access to paediatric trauma centres (PTCs) on patient outcomes, and to determine spatial access to PTCs across Canada. Setting: To examine the relationship between access to PTC and injury outcome, length of stay at the PTC was determined for all injured patients who live within and outside of 60 min driving time of the PTC. To determine spatial access to PTCs across Canada, a list of level 1 and 2 PTCs was identified across Canada. A 1 h driving time catchment was created around each PTC in order to estimate spatial accessibility. Participants: Hospital administration data sets from British Columbia (BC) and the Nova Scotia (NS) trauma registry were used to assess the impact of spatial access on paediatric injury (ages 0–15 years) outcomes. The data sets provided case-level data including the Injury Severity Score, postal code of place of residence, age and length of hospital stay. Results: In NS and BC, average length of stay at the hospital is significantly lower inside 60 min driving time compared to outside of 60 min driving time from a PTC (p<0.05, using a non-parametric t test). In Canada, approximately 65% of the paediatric population resides within 1 h of a PTC. Conclusions: This paper highlights differences in injury outcomes as a result of access. However, further investigation is needed as other considerations such as type of injury, age and/or gender may also affect injury outcomes.